Risk Transfer with Interest Rate Swaps. Issue 1 (21st December 2020) - Baker, Lee; Haynes, Richard; Roberts, John; Sharma, Rajiv; Tuckman, Bruce
Abstract: This paper proposes Entity‐Netted Notionals (ENNs) as a metric of interest rate risk transfer in the interest rate swap (IRS) market. Unlike the ubiquitous metric of notional amount, ENNs normalize for risk and account for the netting of longs and shorts within counterparty relationships. Using regulatory data for U.S.‐reporting entities, the size of the market measured by notional amount is 231 trillion, but, measured by ENNs, is only 13.9 trillion 5‐year swap equivalents, which is the same order of magnitude as other large U.S. fixed income markets. This paper also quantifies the size and direction of IRS positions across and within various business sectors. Among the empirical findings are that 92% of entities using IRS are exclusively long or exclusively short. Hence, the vast majority of market participants are prototypical end users, and the extensive amount of netting in the market is attributable to the activity of relatively few, larger entities. Finally, some sector‐specific empirical findings are inconsistent with widespread, prior beliefs. For example, pension funds and insurance companies are typically thought to be long IRS to hedge their long‐term liabilities, and these sectors are indeed net long, but approximately 50% of individual entities in these sectors are actually net short.